Biallelic loss‐of‐function variants in TBC1D2B cause a neurodevelopmental disorder with seizures and gingival overgrowth. Issue 9 (15th July 2020) - Harms, Frederike L.; Parthasarathy, Padmini; Zorndt, Dennis; Alawi, Malik; Fuchs, Sigrid; Halliday, Benjamin J.; McKeown, Colina; Sampaio, Hugo; Radhakrishnan, Natasha; Radhakrishnan, Suresh K.; Gorce, Magali; Navet, Benjamin; et al.
Abstract: The family of Tre2‐Bub2‐Cdc16 (TBC)‐domain containing GTPase activating proteins (RABGAPs) is not only known as key regulatorof RAB GTPase activity but also has GAP‐independent functions. Rab GTPases are implicated in membrane trafficking pathways, such as vesicular trafficking. We report biallelic loss‐of‐function variants in TBC1D2B, encoding a member of the TBC/RABGAP family with yet unknown function, as the underlying cause of cognitive impairment, seizures, and/or gingival overgrowth in three individuals from unrelated families. TBC1D2B messenger RNA amount was drastically reduced, and the protein was absent in fibroblasts of two patients. In immunofluorescence analysis, ectopically expressed TBC1D2B colocalized with vesicles positive for RAB5, a small GTPase orchestrating early endocytic vesicle trafficking. In two independent TBC1D2B CRISPR/Cas9 knockout HeLa cell lines that serve as cellular model of TBC1D2B deficiency, epidermal growth factor internalization was significantly reduced compared with the parental HeLa cell line suggesting a role of TBC1D2B in early endocytosis. Serum deprivation of TBC1D2B ‐deficient HeLa cell lines caused a decrease in cell viability and an increase in apoptosis. Our data reveal that loss of TBC1D2B causes a neurodevelopmental disorder with gingival overgrowth, possibly by deficits in vesicle trafficking and/or cell survival.